2017
DOI: 10.1002/lom3.10224
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of solid‐phase extraction resins on the measurement of dissolved lignin‐phenols and organic matter composition in natural waters

Abstract: Compositional changes in dissolved organic matter (DOM) matrix via solid phase extraction (SPE) remain under-constrained due to disproportional extraction of specific groups of compounds. This study elucidates changes in the composition of DOM via SPE by presenting an intercomparison of recovery efficiencies of dissolved lignin phenol standards using three SPE cartridges (C-18, PPL and HLB) and an intercomparison of free-lignin phenols and lignin-oxidized products (LOPs) (via SPE) for two end-members (river an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
4
14
0
Order By: Relevance
“…Mean dissolved lignin export was lower in BB (9.65 ± 6.38 × 10 4 kg/year) than in AP (3.48 ± 2.20 × 10 5 kg/year), and mean particulate lignin export was higher in BB (4.76 ± 2.97 × 10 5 kg/year) than in AP (7.34 ± 3.15 × 10 4 kg/year; Table ). The reported dissolved lignin fluxes in this study are likely underestimates due to inefficiencies of Solid‐Phase Extraction‐Priority PolLutant (SPE‐PPL) (41% LOP recovery rates; Arellano et al, ). It was clear the largest fraction of export was particulate lignin from BB, and indeed this fraction was larger even than the export of dissolved lignin from AP.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Mean dissolved lignin export was lower in BB (9.65 ± 6.38 × 10 4 kg/year) than in AP (3.48 ± 2.20 × 10 5 kg/year), and mean particulate lignin export was higher in BB (4.76 ± 2.97 × 10 5 kg/year) than in AP (7.34 ± 3.15 × 10 4 kg/year; Table ). The reported dissolved lignin fluxes in this study are likely underestimates due to inefficiencies of Solid‐Phase Extraction‐Priority PolLutant (SPE‐PPL) (41% LOP recovery rates; Arellano et al, ). It was clear the largest fraction of export was particulate lignin from BB, and indeed this fraction was larger even than the export of dissolved lignin from AP.…”
Section: Discussionmentioning
confidence: 77%
“…DOM was extracted on hydrophilic-lipophilic balanced (HLB) cartridges according to the method of Keil and Neibauer (2009) and Arellano et al (2018). CuO oxidation products were extracted and analyzed according to Hedges and Ertel (1982), as modified by Goñi and Hedges (1995) and further modified by Louchouarn et al (2010).…”
Section: Dissolved and Particulate Lignin Phenolsmentioning
confidence: 99%
“…Hence, the extraction of DON molecules must be taken into account. However, Arellano et al (2017) indicated a low extraction efficiency for DON in coastal samples using the PPL sorbent. On the other side, Spanik et al (2007) showed that strong cation exchange resin can be used for the pre-concentration of amino acids in water samples.…”
Section: Introductionmentioning
confidence: 96%
“…In this case a change in molecular composition of the DOM isolate, which was brought about by a purely methodical bias (molecular selectivity of the new sorbent) can lead to erroneous conclusions and interpretations with regard to the course of environmental processes. The existence of molecular selectivity is numerously reported [17,18]. Our previous studies have shown [18] that a use of Bond ELut PPL cartridges versus Amberlite XAD-8 resin gave very different samples of DOM from the same water: the former were enriched with aliphatic components, whereas the latter were rich in aromatic structures.…”
Section: Introductionmentioning
confidence: 97%
“…Application of Bond Elut PPL cartridges for isolation of the Suwannee River DOM gave DOC recovery results of 89% [16]. Comparison of three types of sorbents (C-18, PPL, and HLB) was reported for DOM and lignin-phenols [17]. It showed that DOC recovery was the best for PPL (60% for rivers and 47% for coastal DOM).…”
Section: Introductionmentioning
confidence: 99%